2009
DOI: 10.1007/s10532-009-9292-9
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of selected (bio-)surfactants by bacterial cultures monitored by calorimetric methods

Abstract: The subjects of the article are investigations concerning the ability of both Rhodococcus opacus 1CP and mixed bacterial cultures to use selected surfactants as sole carbon and energy source. In a comparative manner the biosurfactants rhamnolipid, sophorolipid and trehalose tetraester, and the synthetic surfactant Tween 80 were examined. Particular emphasis was put on a combinatorial approach to determine quantitatively the degree of surfactant degradation by applying calorimetry, thermodynamic calculations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Schippers et al () found that sophorolipids enhanced the ability of Sphingomonas yanoikuyae to degrade phenanthrene and did not affect cell growth of the bacterium. Frank et al () reported sophorolipids can be degraded by micro‐organisms. Therefore, it has the potential to be used as a sustainable and environmental friendly alternative for synthesized chemical surfactants (Chuo et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Schippers et al () found that sophorolipids enhanced the ability of Sphingomonas yanoikuyae to degrade phenanthrene and did not affect cell growth of the bacterium. Frank et al () reported sophorolipids can be degraded by micro‐organisms. Therefore, it has the potential to be used as a sustainable and environmental friendly alternative for synthesized chemical surfactants (Chuo et al ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that octadecenoic acid can be degraded by bacteria which have been isolated from soil. 32 As Fig. 7 shows, aer the rst 25 days, most of the aliphatic acid ester and alcohol had decreased, which means that a large proportion of Tween-80 was reduced during this period.…”
Section: Metabolites In Surfactants Biodegradation Processmentioning
confidence: 88%
“…Because the rhamnolipid can be consumed by microorganisms except for its producing bacterium Pseudomonas aeruginosa, 31 the compounds can be utilized by bacteria in soil. 32 During the rst degradation process, most of the rhamnolipid structures were transformed into alkyl acid and a few alkanes with different carbon chains. Tetracosanoic acid, octadecanoic acid (Z)-9-octadecenamide can be also attained.…”
Section: Metabolites In Surfactants Biodegradation Processmentioning
confidence: 99%
“…It is often highlighted that biosurfactants are biodegraded easier than chemical surfactants (Mulligan 2005 ), but fast biodegradation of an exogenously added biosurfactant may not only be advantageous, as fast degradation may limit its potential for usage in bioremediation. However, the stability of biosurfactants is rarely investigated in alkane biodegradation studies (Frank et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%